2017
DOI: 10.4103/1319-2442.220846
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anemia in a kidney transplant recipient with parvovirus B19 infection

Abstract: Anemia after kidney transplant is not uncommon. This paper reports a case of unexplained anemia in a kidney transplant recipient that persisted for more than two months, and that did not respond to recombinant human erythropoietin treatment but was successfully treated after diagnosing Parvovirus B19 (ParvoV B19) infection. A middle-aged male underwent living-unrelated kidney transplantation from Pakistan in April 2015. He was on triple immuno-suppression therapy consisting of prednisolone, tacrolimus, and myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The most common clinical manifestations of parvovirus in immunocompromised patients are arthralgia fever and anemia rash, and lack of response to erythropoietin (5). Parvovirus can be accompanied by hepatitis, myocarditis, pneumonitis, and graft dysfunction in transplant patients (3), as in our patient.…”
Section: Discussionmentioning
confidence: 79%
“…The most common clinical manifestations of parvovirus in immunocompromised patients are arthralgia fever and anemia rash, and lack of response to erythropoietin (5). Parvovirus can be accompanied by hepatitis, myocarditis, pneumonitis, and graft dysfunction in transplant patients (3), as in our patient.…”
Section: Discussionmentioning
confidence: 79%
“…9 Fever, rash, arthralgia, normochromic normocytic anemia, and lack of response to erythropoietin are the most common manifestations of PB19 infection in immunosuppressed patients. 10 PB19 infection may involve other organs, leading to myocarditis, pneumonitis, hepatitis, and graft failure. 3,11 In our patient, the clinical suspicion of erythrocyte-involving infection, such as PB19, was raised due to the decrease in erythrocyte levels as well as the lack of evidence of common causes of anemia, including gastrointestinal or urinary bleeding, hemolysis, or malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunocompromised patients may experience persistent infection owing to insufficient antiviral antibody production, leading to pure red blood cells aplasia (PRCA) 9 . Fever, rash, arthralgia, normochromic normocytic anemia, and lack of response to erythropoietin are the most common manifestations of PB19 infection in immunosuppressed patients 10 . PB19 infection may involve other organs, leading to myocarditis, pneumonitis, hepatitis, and graft failure 3,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boaek et al indicated deceased donor kidney transplantation, tacrolimus treatment, and decreased hemoglobin concentration as factors correlating significantly in multivariate analysis with PV B19 infection within the first-year after kidney transplantation [24]. Approximately 50 cases of PV B19 related PRCA in adult kidney recipients have been described in the literature to date [18,23,2563], (see Table 3). PRCA was diagnosed from 4 days to 160 weeks after kidney transplantation, usually within the first year [25,59].…”
Section: Discussionmentioning
confidence: 99%